The phenotype of the gut region is more stably retained than developmental stage in piglet intestinal organoids - Mussard, Eloïse; Lencina, Corinne; Gallo, Lise; Barilly, Céline; Poli, Maryse; Feve, Katia; Albin, Mikael; Cauquil, Laurent; Knudsen, Christelle; Achard, Caroline; Devailly, Guillaume; Soler, Laura; et al. (Frontiers in Cell and Developmental Biology, 2022)
Intestinal organoids are innovative in vitro tools to study the digestive epithelium. The objective of this study was to generate jejunum and colon organoids from suckling and weaned piglets in order to determine the extent to which organoids retain a location-specific and a developmental stage-specific phenotype. Organoids were studied at 3 time points by gene expression profiling for comparison with the transcriptomic patterns observed in crypts in vivo. In addition, the gut microbiota and the metabolome were analyzed to characterize the luminal environment of epithelial cells at the origin of organoids. The location-specific expression of 60 genes differentially expressed between jejunum and colon crypts from suckling piglets was partially retained (48%) in the derived organoids at all time point. The regional expression of these genes was independent of luminal signals since the major differences in microbiota and metabolome observed in vivo between the jejunum and the colon were not reproduced in vitro. In contrast, the regional expression of other genes was erased in organoids. Moreover, the developmental stage-specific expression of 30 genes differentially expressed between the jejunum crypts of suckling and weaned piglets was not stably retained in the derived organoids. Differentiation of organoids was necessary to observe the regional expression of certain genes while it was not sufficient to reproduce developmental stage-specific expression patterns. In conclusion, piglet intestinal organoids retained a location-specific phenotype while the characteristics of developmental stage were erased in vitro. Reproducing more closely the luminal environment might help to increase the physiological relevance of intestinal organoids.